Where Do STEM Graduates Stem From? The Intergenerational Transmission of Comparative Skill Advantages - Eric A. Hanushek; Babs Jacobs; Guido Schwerdt; Rolf Van der Velden; Stan Vermeulen; Simon Wiederhold (Institute of Labor Economics (IZA), 2023)
The standard economic model of occupational choice following a basic Roy model emphasizes individual selection and comparative advantage, but the sources of comparative advantage are not well understood. We employ a unique combination of Dutch survey and registry data that links math and language skills across generations and permits analysis of the intergenerational transmission of comparative skill advantages. Exploiting within-family between-subject variation in skills, we show that comparative advantages in math of parents are significantly linked to those of their children. A causal interpretation follows from a novel IV estimation that isolates variation in parent skill advantages due to their teacher and classroom peer quality. Finally, we show the strong influence of family skill transmission on children's choices of STEM fields.
Keywords: I24; I26; J12; J24; J62; 330; intergenerational mobility; parent-child skill transmission; causality; STEM